ENHANZE® drug delivery technology : advancing subcutaneous drug delivery using recombinant human hyaluronidase PH20 - Bittner, Beate; Locke, Kenneth W.; Maneval, Daniel C.; Flamion, Bruno; Connor, Robert J.; Kang, David W.; Tannenbaum, Renee (UK : Karger, 2022)
'ENHANZE® drug delivery technology: Advancing subcutaneous drug delivery using recombinant human hyaluronidase PH20' provides readers with in-depth information on the potential benefits and challenges of subcutaneous (SC) drug delivery, the biology of hyaluronan and hyaluronidases in the SC space, and a comprehensive overview on the history of hyaluronidases and the development of recombinant human hyaluronidase PH20 (rHuPH20). Current applications of rHuPH20 as well as approved biotherapeutics utilizing HuPH20-facilitated SC drug delivery are summarized, and the underlying non-clinical and clinical development approaches are introduced as a basis for future application to biologics in various disease areas.
Keywords: HIALURONIDASA -- USO TERAPÉUTICO -- ADMINISTRACIÓN; INYECCIONES HIPODERMICAS; ADMINISTRACIÓN DE DROGAS